Juridical Analysis of The Application of Diversion in Child Crime Cases to Realize Restorative Justice at The Court Level - La Gurusi (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The problem to be investigated is how the application of diversion in realizing Restorative Justice at the Pasarwajo District Court level and the obstacles to the application of Diversion in realizing Restorative Justice at the Pasarwajo District Court level. The objectives and benefits to be achieved in this study are to find out how the application of Diversion in realizing Restorative Justice at the Pasarwajo District Court level and can help and provide input and additional knowledge for parties related to the problems studied. This research is an empirical juridical research that uses primary data as its study material. The result of this research is that the application of Diversion in realizing Restorative Justice at the Pasarwajo District Court still has obstacles.